Murmure - Arcuri, Serge, 1954- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1989)
Murmure is an electroacoustic piece for magnetic tape alone. It was created at the request of David Olds as part of the radio show "Transfigured Night". There are many myths that attribute the creation of the universe to a breath or a cry. From primitive African societies to Vedic texts in India, in China or among the Inuit peoples, we find universally a sound at the origin of the different cosmogonies. The astrophysical theories of the twentieth century do not designate the first seconds of the universe by the term "Big Bang". Murmure weaves in a few minutes the long course of the original breath to the human voice. The piece is both part of a musical theater on the dream called Meander.